2021
DOI: 10.1111/ctr.14556
|View full text |Cite
|
Sign up to set email alerts
|

Anonymous living liver donor perspectives on the role of family in their donation experience

Abstract: Anonymous living organ donation is an understudied but rapidly expanding sector in organ transplantation, in which donors choose to donate anonymously to a recipient in need. The family members and close support network of living donors often play a crucial role in the donation process, and their influence likely has a large impact on the decision to donate as well as the donor's physical and psychosocial state. However, there is limited data examining the impact donor families have on the anonymous donor, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…in the United Kingdom [20][21][22], the United States [23][24][25], Canada [26][27][28], New Zealand [29], the Netherlands [30], and Sweden [31]. In total, there were 163 unspecified living kidney donors and 26 living liver donors, of whom 129 kidney donors and all 26 liver donors completed donation at time of study.…”
Section: Plos Onementioning
confidence: 99%
See 3 more Smart Citations
“…in the United Kingdom [20][21][22], the United States [23][24][25], Canada [26][27][28], New Zealand [29], the Netherlands [30], and Sweden [31]. In total, there were 163 unspecified living kidney donors and 26 living liver donors, of whom 129 kidney donors and all 26 liver donors completed donation at time of study.…”
Section: Plos Onementioning
confidence: 99%
“…The dominant reaction of family and friends was disapproval or active opposition and donors were largely perceived as being either 'mad' or 'brave' which resulted in feelings of frustration and embarrassment [20-23, 26, 27]. Donors reported that their families were worried and feared for the donor's life and safety [20,27]. Conversely, some stated that their families were supportive and emphasized the importance of emotional support from their loved ones during the donation process [22,[26][27][28].…”
Section: Donor Supportmentioning
confidence: 99%
See 2 more Smart Citations